Rural–urban human capital disparity and skilled–unskilled wage inequality in China. Issue 2 (29th December 2017) - Pi, Jiancai; Zhang, Pengqing
Abstract: This paper builds three‐sector general equilibrium models to investigate how a shrink of rural–urban human capital disparity generates an impact on skilled–unskilled wage inequality in China. In the basic model where the urban skilled sector and the urban unskilled sector have no upstream and downstream linkage, we find that the wage inequality will be narrowed down if the urban skilled sector is more capital intensive than the urban unskilled sector. To capture the characteristic of China's state capitalism, we build an extended model where the urban skilled sector acts as an upstream industry for the urban unskilled sector, and find that the wage inequality will be reduced if the substitution elasticity of unskilled labor and intermediate product in the urban unskilled sector is large enough. When we consider the factual characteristics of the Chinese economy, our models predict that a shrink of rural–urban human capital disparity will be helpful to reduce the skilled–unskilled wage inequality in China.